2003
DOI: 10.1071/as02041
|View full text |Cite
|
Sign up to set email alerts
|

Constraining the Evolution of Young Radio-Loud AGN

Abstract: GPS and CSS radio sources are the objects of choice to investigate the evolution of young radioloud AGN. Previous investigations, mainly based on number counts and source size distributions, indicate that GPS/CSS sources decrease significantly in radio power when evolving into old, extended objects. We suggest this is preceded by a period of increase in radio luminosity, which lasts as long as the radio source is confined within the core-radius of its host galaxy. We have selected a sample of nearby compact ra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 23 publications
1
29
0
Order By: Relevance
“…Readhead et al (1996) proposed an evolutionary scheme unifying three classes of objects: compact symmetric objects (CSOs), MSOs, and LSOs. Snellen et al (1999Snellen et al ( , 2000Snellen et al ( , 2003 discussed many aspects of the above scenario in detail. In particular they concluded that the radio luminosity of GPS/CSO objects increases as they evolve, reaches its maximum for the CSS/MSO phase, and then gradually decreases as these objects grow further to become LSOs.…”
Section: Only Fr II or Either Fr I Or Fr Ii?mentioning
confidence: 99%
“…Readhead et al (1996) proposed an evolutionary scheme unifying three classes of objects: compact symmetric objects (CSOs), MSOs, and LSOs. Snellen et al (1999Snellen et al ( , 2000Snellen et al ( , 2003 discussed many aspects of the above scenario in detail. In particular they concluded that the radio luminosity of GPS/CSO objects increases as they evolve, reaches its maximum for the CSS/MSO phase, and then gradually decreases as these objects grow further to become LSOs.…”
Section: Only Fr II or Either Fr I Or Fr Ii?mentioning
confidence: 99%
“…Relative number statistics indicated that at a young age, radio sources must have significantly higher radio luminosities than at a later stage (O'Dea & Baum 1996;Readhead et al 1996;Fanti & Fanti 2003). This decrease in radio luminosity may be preceded by a period of luminosity increase (Snellen et al 2000b(Snellen et al , 2003.…”
Section: Introductionmentioning
confidence: 99%
“…Relative number statistics have indicated that these radio sources must be significantly more powerful at young ages, which may be preceded by a period of luminosity increase (e.g. Snellen et al 2003). Multi-epoch VLBI observations of individual Gigahertz Peaked Spectrum and Compact Symmetric Objects indicate dynamical ages in the range of a few hundred to a few thousand years (e.g.…”
Section: Introductionmentioning
confidence: 99%